Pharmacological and Behavioral Treatment of Opioid Use Disorder. Issue 1 (5th December 2018) - Sofuoglu, Mehmet; DeVito, Elise E.; Carroll, Kathleen M.
Abstract : Objective: Opioid use disorder (OUD) in the United States has surged, with an estimated 2.5 million needing treatment. The aim of this article is to provide a clinical overview of the key pharmacological and behavioral treatments for OUD. Methods: A nonsystematic review of the literature was conducted to investigate OUD treatments, including their mechanism of action, efficacy, clinical guidelines in the United States, and consideration of frequently occurring comorbid conditions. Results: Food and Drug Administration (FDA)–approved pharmacotherapies for OUD include methadone, buprenorphine, and naltrexone, each of which has different actions on opioid receptors. Although these medications all show efficacy in some dosages and formulations, barriers to accessibility may be most pronounced for methadone, whereas treatment retention poses greater challenges for naltrexone and, to a lesser extent, buprenorphine. Lofexidine, an α2 ‐adrenergic agonist, has recently been approved by the FDA for treatment of opioid withdrawal symptoms. OUD is commonly treated with medication‐assisted treatment (MAT), which offers pharmacotherapy in the context of counseling and/or behavioral treatments. Behavioral therapies, rarely offered as stand‐alone treatments for OUD, are generally used in the context of MAT, in structured settings or to prevent relapse after detoxification and stabilization. The aim of behavioral interventions is to improve medication compliance and target problems not addressed with medication alone. Individuals with OUD commonly have other comorbid psychiatric and substance use conditions, which are not exclusionary for initiating MAT but should be carefully evaluated and monitored because they may reduce treatment effectiveness. Conclusions: MAT is the first‐line treatment for patients with OUD and should be provided in combination with behavioral interventions. Treatment retention remains challenging in this population. Future studies should focus on approaches that will serve the complex needs of patients with OUD, including those with comorbid psychiatric and substance use conditions.